Consumer Value in Complementary and Alternative Medicine (CAM) Health Care Services. Issue 3 (August 2014) - Dodds, Sarah; Bulmer, Sandy; Murphy, Andrew
Complementary and Alternative Medicine (CAM) is a fast growing health care service warranting further research to understand its place in modern healthcare. This study investigated what consumers of CAM value from their healthcare experiences. The research adopted an interpretive approach using in-depth interviews with 12 CAM consumers. Seven consumer value components were identified 1) quality of care, 2) treatment efficiency, 3) physical environment, 4) social (esteem) value, 5) spiritual value, 6) ethics (natural aspect), 7) play (relaxation, leisure activities). Findings indicate that CAM consumers evaluate the value of their healthcare experience primarily on quality of care (which revolved around an empowering partnership) and treatment efficiency (such as treatment results and treatment ease of use and customisation) with the physical environment playing a small role. It was through valuing these experiences that the CAM consumer then began to value the other consumer value components – spiritual value, social value, ethics and play. We propose a consumer value model that is relevant to the CAM health care setting, and conclude that the key aspects that CAM consumers value has managerial implications for both CAM and mainstream health providers.